2023
DOI: 10.34133/research.0140
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Defect-Induced Ice Nucleation, Propagation, and Adhesion by Bioinspired Self-Healing Anti-Icing Coatings

Abstract: Anti-icing coatings on outdoor infrastructures inevitably suffer from mechanical injuries in numerous icing scenarios such as hailstorms, sandstorms, impacts of foreign objects, and icing–deicing cycles. Herein, the mechanisms of surface-defect-induced icing are clarified. At the defects, water molecules exhibit stronger adsorption and the heat transfer rate increases, accelerating the condensation of water vapor as well as ice nucleation and propagation. Moreover, the ice–defect interlocking structure increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Comparative analysis indicated that the B-PDMS coating exhibited a significantly lower ice adhesion strength than most reported values in the literature, underscoring its ability to delay the icing process. 55–58…”
Section: Resultsmentioning
confidence: 99%
“…Comparative analysis indicated that the B-PDMS coating exhibited a significantly lower ice adhesion strength than most reported values in the literature, underscoring its ability to delay the icing process. 55–58…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the currently reported anti-icing coatings internationally, this coating can not only self-heal at low temperatures but also simultaneously inhibit ice nucleation, transfer, and adhesion. It has environmental adaptability and large-scale coating potential, providing new ideas for the development of anti-icing coatings applied in outdoor environments that are prone to damage [125].…”
Section: Research Progressmentioning
confidence: 99%
“…31,33 In addition, SHSs used outdoors are prone to mechanical damage from the outside, causing damage to their surface structure and increasing the mechanical interlocking between ice and damaged surfaces. 34 Lately, the self-healing function has been added to SHSs to counteract the reduction in superhydrophobicity brought on by significant mechanical damage. 35,36 This innovation was motivated by the biological regeneration features found in living organisms.…”
Section: ■ Introductionmentioning
confidence: 99%